A prospective randomized controlled study comparing short-term outcomes of closure and non-closure of peritoneum during elective caesarean section - Prabhu, Santoshi; Prasad, Deepti N.; Mishra, Nigamanand; Jadhav, Vaishali; Savani, Gayatri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: There is a rising trend of caesarean deliveries worldwide. Although a very commonly performed abdominal surgery, there is no ideal operative procedure in the literature. Several studies compared short term and long-term outcomes of closure and non-closure of peritoneum, but there is no consensus whether either procedure is beneficial to patients. Variability of results may be due to bias involved in these studies as two groups compared had different characteristics (including obstetrics and non-obstetrics laparotomies, elective and emergency caesareans, Pfannenstiel as well as vertical incisions; in the same study) which are likely to affect short term outcomes besides those due to peritoneal closer and non-closure. Aims and objectives of the study were to perform an unbiased assessment of short-term outcomes in elective LSCS in unscarred abdomens by Pfannenstiel incisions between closure (CG) and non-closure of peritoneum (NCG). Methods: Prospective randomised controlled study method used in the study. Results: The operating time was significantly more (p=0.01) with difference of additional 10 minutes in CG with standard error of mean for time being 3.7688. Pain score was more in CG on post-operative day 1 and 2 (p=0.0003 and 0.008 respectively). Additional anaesthesia and analgesia were not needed in this group. Conclusions: Apart from operative timing and pain score in early post-op period, there was no significant difference in short term outcomes between CG and NCG during elective caesarean section. Hence only long-term effects of these procedures need to be considered prior to recommending ideal steps of elective caesarean section procedure.